CS Unplugged: Experiences and Extensions - Demšar, Irena; Demšar, Janez (Informatics in Schools. Curricula, Competences, and Competitions, 2015)
CS Unplugged is a set of activities for teaching CS concepts without using computers. We translated it to Slovenian and used it in different contexts, from the classroom and afterschool activity to summer school to professional development courses. In the paper, we summarize our adaptations, extensions and experiences.